(3QDjI GbJUGOjIs - (3HGSe GMeO(B, (3YGeQs ((3YeGf(B:s (3OGQ GdfaGFS(B,s, 2010)
1) (3fXQjI GdGfaGb (B: (3eaghe fXQjI GdGfaGb h CQcGfgG , CgejI GdGfaGb aj GdbQBf h OhQg aj GdMjGI GdGbJUGOjI , GdGfaGb aj GdacQ GdhVYj , (B2) (3CfhGY GdGfaGb h OdGdGJgG GdGbJUGOjI aj GdbQBf GdcQje (B: (3GdGfaGb GdeMehO h GdePehe h GdGfaGb GdYGe h GddNGU h GdGfaGb GdGLJeGYj aj GdbQBf GdcQje , (B3)(3CKQ GdGfaGb aj VhA GdbQBf GdcQje Ydi GdfTGW GdGbJUGOj (B: (3GdGfaGb h GdGSJgdGc , GdGfaGb h GdGSJJKeGQ , GdGfaGb h JNUjU GdehGQO , GdGfaGb h GdWHbGJ GdGLJeGYjI h GdGfaGb h GdJfejI GdGbJUGOjI (B4) (3eXGgQ GdJhGRf aj GdGfaGb aj VhA GdbQBf GdcQje (B: (3GdGfaGb Hjf GdGSQGa h GdJbJjQ , GdGfaGb Hjf GdaQO h GdLeGYI , GdGfaGb Hjf GdOfjG h GdBNQI h GdGfaGb Hjf GdSQ h GdYdGfjI (B.s
(3eQGLY U(B.217s
Keywords: (3GdEbJUGO GdESdGejs; (3GdeGdjI GdYGeIs; (3GdfabIs